2010
DOI: 10.1007/s11414-009-9205-z
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Social Networks and Social Support on Mental Health Services Use, Following a Life Event, among the Baltimore Epidemiologic Catchment Area Cohort

Abstract: The study examined the association between life events and mental health services use, accounting for social networks and social support. Main and stress-buffering effects were estimated using longitudinal data from the Baltimore Epidemiologic Catchment Area cohort (1,920 participants in 1993-1996, of whom 1,071 were re-interviewed in 2004-2005). Following a life event, the odds of using general medical services were increased by almost 50% when there was increased social support from spouse/partner (referral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
67
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 41 publications
(46 reference statements)
3
67
2
Order By: Relevance
“…Link and colleagues 34 conclude that the stigma associated with belonging to a stigmatized group may be expressed through discrimination, separation, and loss of status. Lack of social support may lead to depression 37 and drug use relapse. 38 Drug user stigma may also lead to rejection by non-drug users 34 and greater affiliation with other drug users.…”
Section: Introductionmentioning
confidence: 99%
“…Link and colleagues 34 conclude that the stigma associated with belonging to a stigmatized group may be expressed through discrimination, separation, and loss of status. Lack of social support may lead to depression 37 and drug use relapse. 38 Drug user stigma may also lead to rejection by non-drug users 34 and greater affiliation with other drug users.…”
Section: Introductionmentioning
confidence: 99%
“…This argument is supported by studies that have found that perceived support mediates the effect of structural support on mental health problems or is a stronger predictor of mental health problems [16,17,21,[58][59][60][61] or of health care utilization [62,63] than structural support. However, concerns have arisen that perceived social support might be influenced by negative mood states [64].…”
Section: Introductionmentioning
confidence: 88%
“…Additionally, more social support has been associated with less use of mental health services. 13 Older adults tend to report fewer social contacts than other age groups do, 22 suggesting that the association between social support and obtaining mental health may be significant for old er but not younger adults. The existing research on predisposing and need factors associated with obtaining mental health care has yet to examine the interaction of age with these factors.…”
Section: Age As Moderator Of Associations Between Predisposing and Nementioning
confidence: 99%
“…For example, among individuals with depression, those with broader social support were less likely to obtain mental health care. 8,13 In dividuals with more social support may not obtain mental health care as frequently as those with low levels of social support due to receiving more in formal support from friends and family members. 6 Thus, smaller networks and less support appear to be predisposing factors for use of mental health services.…”
mentioning
confidence: 99%